(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The present paper discusses about Tagore‟s novels which merit genuine notice. They are primary exemplary photos of the Bengal of Tagore‟s time. His novel „Gora‟ is the best novel in Bengal writing. Its totality and closeness of perception have been trailed by his successors. In „Home and the World‟, Tagore delineates the meaner side of awesome against parcel development in which he took so unmistakable an offer. Blemish has a residential plot, spinning around the saint Mahendra. Wreck attempts mental investigation of the characters of the novel.